2021
DOI: 10.1038/s41598-021-82161-z
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-associated disease burden in mainland China: a systematic review and meta-analysis

Abstract: Influenza causes substantial morbidity and mortality. Many original studies have been carried out to estimate disease burden of influenza in mainland China, while the full disease burden has not yet been systematically reviewed. We did a systematic review and meta-analysis to assess the burden of influenza-associated mortality, hospitalization, and outpatient visit in mainland China. We searched 3 English and 4 Chinese databases with studies published from 2005 to 2019. Studies reporting population-based rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
(108 reference statements)
6
21
1
Order By: Relevance
“…25 , 26 , 27 Under the stronger interconnection among intensive population with different living conditions, dynamic of ILI was confirmed to be aggravated, particularly among those susceptible populations like children and adolescents under 25 years. 1 , 15 , 28 , 29 ILI activity among people aged over 25 years remained at a low level, which is in line with previous studies. 15 , 29 , 30 It suggests that influenza prevention and control in newly developed urbanization areas should be focused at places like schools and kindergartens in facing the assault of increasing population diversity, mobility, and human contact.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…25 , 26 , 27 Under the stronger interconnection among intensive population with different living conditions, dynamic of ILI was confirmed to be aggravated, particularly among those susceptible populations like children and adolescents under 25 years. 1 , 15 , 28 , 29 ILI activity among people aged over 25 years remained at a low level, which is in line with previous studies. 15 , 29 , 30 It suggests that influenza prevention and control in newly developed urbanization areas should be focused at places like schools and kindergartens in facing the assault of increasing population diversity, mobility, and human contact.…”
Section: Discussionsupporting
confidence: 92%
“…31 As older adults aged over 65 years were claimed to be with the highest burden of influenza‐related death, the current prevention measures should be maintained as a solid issue. 1 And the correlation analysis further suggested that influenza vaccination offered positive efforts in preventing the school‐aged and elder population from ILI infection. This is in also in line with previous studies that indicate influenza vaccination shows effectiveness in ILI prevention.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mortality of seasonal in uenza in mainland China was from 0.012/100 000 in 2010 to 0.019/100 000 in 2019. However, it is estimated that in uenza-associated all-cause mortality was 14.33/100 000 in mainland China [27], which was much higher than the present study. Previous study pointed out that the death burden of seasonal in uenza had been underestimated, owing to the deaths of seasonal in uenza and other respiratory diseases that are di cult to distinguish [2].…”
Section: Discussioncontrasting
confidence: 85%
“…Excess death rates for elderly were estimated to be over six times higher than in general population with the most of influenza‐related deaths (65%–96%) occurring in persons 65+ 34,36 . These data were also confirmed by other systematic reviews 17,38 …”
Section: Discussionmentioning
confidence: 61%